Women’s Choice, Satisfaction, and Compliance with Contraceptive Methods in Selected Hospitals of Ibadan, Nigeria (2018)
Background & aim: Population control has remained an issue of concern to many developing nations. Many women have unmet needs for contraception. Despite the available options for abortion, unwanted pregnancies account for a high maternal mortality rate. Regarding this, the present study aimed to investigate the choices, satisfaction, and compliance with contraceptive use among the women living in Ibadan, Nigeria. Methods: This cross-sectional study was conducted on 290 women attending the pediatric welfare clinics in four hospitals in 2015. The study population was selected through purposive sampling technique. The data were collected using a self- administered questionnaire. The data were analyzed using descriptive statistics and Chi-square test through SPPS, version 16. Results: According to the results, 95% of the participants were aware of the contraceptive methods, and 72.1% of them had used these methods. Partner's refusal was the major reason for non-use of contraceptives. The birth control methods, which were commonly utilized, were natural family planning (36.5%) and oral contraceptives (30.8%). Furthermore, up to 60% of the subjects were satisfied with the method they used, and 70% of them adhered to the chosen methods. Additionally, compliance with contraceptive methods had a significant association with partners' approval (P=0.038) and satisfaction with contraceptive methods (P=0.04). Conclusion: As the findings of the present study revealed, partners' approval of contraceptives had a significant role in the use of the birth control methods. Furthermore, some women were not satisfied with the methods they used. Regarding the findings of the study, the partners should be involved and well informed about contraceptives in order to enhance their use of contraceptives. Moreover, the women should be provided with appropriate information to be able to make an informed decision for choosing the suitable contraceptive methods.